A systematic review and meta‐analysis of the prevalence and correlation of mild cognitive impairment in sarcopenia. Issue 1 (18th December 2022) - Yang, Ying; Xiao, Mengmeng; Leng, Lin; Jiang, Shixie; Feng, Lei; Pan, Gaofeng; Li, Zheng; Wang, Yan; Wang, Jiang; Wen, Yanting; Wu, Dan; Yang, Yongxue; et al.
Abstract: Sarcopenia is a progressive skeletal muscle disorder involving the loss of muscle mass and function, associated with an increased risk of disability and frailty. Though its prevalence in dementia has been studied, its occurrence in mild cognitive impairment (MCI) has not been well established. As MCI is often a prelude to dementia, our study aims to investigate the prevalence of MCI among individuals with sarcopenia and to also ascertain whether sarcopenia is independently associated with MCI. The Cochrane Library, PubMed, Ovid, Embase and Web of Science were systematically searched for articles on MCI and/or sarcopenia published from inception to 1 February 2022. We reviewed the available literature on the number of individuals with MCI and/or sarcopenia and calculated odds ratios (ORs) of sarcopenia in MCI and MCI in sarcopenia, respectively. Statistical analyses were performed using the meta package in Stata, Version 12.0. A total of 13 studies and 27 428 patients were included in our analysis. The pooled prevalence of MCI in participants with sarcopenia was 20.5% (95% confidence interval [CI]: 0.140–0.269) in a total sample of 2923 cases with a high level of heterogeneity ( P < 0.001; I 2 = 95.4%). The overall prevalence of sarcopenia with MCI was 9.1% (95% CI: 0.047–0.134, P < 0.001; I 2 = 93.0%). For overall ORs, there were 23 364 subjects with a mean age of 73 years; the overall adjusted OR between MCI and sarcopenia was 1.46 (95% CI: 1.31–1.62). Slight heterogeneity in both adjusted ORs ( P = 0.46; I 2 = 0%) was noted across the studies. The prevalence of MCI is relatively high in patients with sarcopenia, and sarcopenia may be a risk factor for MCI.